2008
DOI: 10.1007/s10943-008-9203-0
|View full text |Cite
|
Sign up to set email alerts
|

The Daily Spiritual Experiences Scale and Well-Being: Demographic Comparisons and Scale Validation with Older Jewish Adults and a Diverse Internet Sample

Abstract: A substantive literature connects spirituality to positive physical, social, and mental health. In this study, the Daily Spiritual Experiences Scale (DSES) was administered to 410 subjects who participated in a community study and to 87 residents at the Hebrew Home for the Aged at Riverdale (HHAR), the latter sample consisting primarily of older Jewish respondents. Internal consistency of the DSES in both samples was high and exploratory factor analyses revealed one dominant factor and a second factor, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 31 publications
8
37
0
7
Order By: Relevance
“…Positive associations of DSE's with health were independent of public religious activity in the GSS [36]. Kalkstein and Tower [20] also showed positive correlation of DSE's with self-rated health.…”
Section: Dses and Physical Health-related Outcomesmentioning
confidence: 79%
See 3 more Smart Citations
“…Positive associations of DSE's with health were independent of public religious activity in the GSS [36]. Kalkstein and Tower [20] also showed positive correlation of DSE's with self-rated health.…”
Section: Dses and Physical Health-related Outcomesmentioning
confidence: 79%
“…They have been useful in studies of altruism and self-giving behaviors and attitudes, particularly when motivation is of interest. Lower levels of daily spiritual experiences correlated with having fewer close friends among a mixed sample of 409 adults and 84 older adults [20]. In a longitudinal study of older adults, positive association was found between social network integration and spiritual experiences in older adults [39].…”
Section: Dses and Relationship Outcomesmentioning
confidence: 87%
See 2 more Smart Citations
“…Underwood developed the DSES through extensive qualitative research, and tested the measure for validity and reliability (Underwood 2006). Follow-up studies have confirmed the reliability and validity of the measure among diverse populations, including non-white, non-US and non-Christian respondents (Bailly and Roussiau 2010;Kalkstein and Tower 2009;Loustalot et al 2006;Mayoral et al, in press;Ng et al 2009). Over sixty-five studies have used the DSES, but most have examined the scale's relationship to physical health outcomes and psychological wellbeing (Underwood 2010).…”
Section: Introductionmentioning
confidence: 99%